Metabolic Features of Melanoma: A Gold Mine of New Therapeutic Targets? - Marchetti, Philippe; Guerreschi, Pierre; Kluza, Jerome; Mortier, Laurent (Current Cancer Drug Targets, 2014)
In recent years, our knowledge regarding the metabolism of melanoma has greatly advanced and consequently new therapeutic strategies are being developed. This review is focused on metabolic pathways contributing to melanoma proliferation, the influence of BRAF inhibitors on those metabolic pathways and finally a presentation of potential therapeutic strategies aimed at blocking metabolic signaling pathways and therefore melanoma development.
Keywords: Glycolysis